2015
DOI: 10.5045/br.2015.50.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation and expression levels of selected hematopoietic genes in pediatric B-cell acute lymphoblastic leukemia

Abstract: BackgroundPrecursor B-cell acute lymphoblastic leukemia (B-cell ALL) is the most common neoplasm in children and is characterized by genetic and epigenetic aberrations in hematopoietic transcription factor (TF) genes. This study evaluated promoter DNA methylation and aberrant expression levels of early- and late-acting hematopoietic TF genes homeobox A4 and A5 (HOXA4 and HOXA5), Meis homeobox 1 (MEIS1), T-cell acute lymphocytic leukemia 1 (TAL1), and interferon regulatory factors 4 and 8 (IRF4 and IRF8) in ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Thus, TAL1 promoter methylation may result in impaired hematopoietic differentiation and contribute to leukemogenic transformation and prognosis of leukemia. Indeed, a comparison of the methylation levels between cases who developed ALL relapse (n = 7) and those who did not (n = 31) showed a slight increase in the TAL1 promoter methylation level for relapse patients (median value 1.693 vs. 0%, p = 0.0129) [21] . However, the prognostic value of TAL1 hypermethylation in ALL needs to be validated in a larger number of patients, possibly using different DNA methylation techniques.…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, TAL1 promoter methylation may result in impaired hematopoietic differentiation and contribute to leukemogenic transformation and prognosis of leukemia. Indeed, a comparison of the methylation levels between cases who developed ALL relapse (n = 7) and those who did not (n = 31) showed a slight increase in the TAL1 promoter methylation level for relapse patients (median value 1.693 vs. 0%, p = 0.0129) [21] . However, the prognostic value of TAL1 hypermethylation in ALL needs to be validated in a larger number of patients, possibly using different DNA methylation techniques.…”
Section: Dna Methylationmentioning
confidence: 99%
“…These studies suggest that changes in promoter methylation may be associated with relapse. The top methylated genes identified so far are T-cell acute lymphocytic leukemia 1 (TAL1) [21] , endogenous retrovirus group H, member 3 (ERHV-3) [22] , cyclin-dependent kinase inhibitor 2A (CDKN2A) [23] , CALCA [24,25] , and p15 [26,27] .…”
Section: Dna Methylationmentioning
confidence: 99%
“…In the context of hematologic malignancies, DNMT overexpression has been observed in samples from leukemia patients [27]. These previous findings collectively suggest that dysregulated DNA hypermethylation may lead to gene silencing, thereby triggering leukemogenesis [28,29].…”
Section: Discussionmentioning
confidence: 98%
“…MEIS1 and HOXA4 expression and TAL1 methylation are correlated with WBC count, National Cancer Institute (NCI) risk classification and age, respectively. MEIS1 expression is inversely associated with WBC count, HOXA4 expression is down-regulated in patients with high risk based on the NCI classification and TAL1 methylation is rather increased in patients older than 9 years and in patients who show relapse (129). It has also been demonstrated that increased histone H4 acetylation is significantly associated with favorable RFS, EFS, OS in pediatric BCP-ALL (130).…”
Section: Epigenetic-based Biomarkersmentioning
confidence: 99%